POTENSI KITOSAN DARI CANGKANG INTERNAL CUMI SEBAGAI ADSORBEN LOGAM BERAT TIMBAL (Pb) DI PERAIRAN SUNGAI TALLO SULAWESI SELATAN - Fadilla, A. Ainur; Nurrahmi, Sitti; Rani, Sefrilita Risqi Adikaning (Prodi Fisika FST UNJA, 2025)
Heavy metal pollution in aquatic environments is one of the serious problems that threaten the health of ecosystems and humans. Various methods have been developed to overcome this pollution, one of which is using natural materials such as chitosan. This study aims to explore the potential of chitosan produced from squid (Loligo sp.) internal shells as heavy metal adsorbents in filtration systems. Chitosan is a biopolymer known to have a high ability to bind metal ions through its amino and hydroxyl groups. In this study, chitosan was synthesized through several processes, namely Deproteination, mineralization and deacetylation of chitin extracted from squid internal shells. The resulting chitosan was characterized using infrared spectroscopy (FTIR) to identify groups formed from the chitin deacetylation process. The results showed that chitosan based on squid internal shells has an adsorption capacity that meets the standard water content of 2%, ash content of 1% and Deacetyl Degree (DD) of 82.8%. Based on the characterization of functional groups using FTIR, the hydroxyl group -OH and the amine group (-NH2) play a significant role in the heavy metal adsorption process. Because these groups are able to form complex bonds with heavy metal ions. Application in the absorption of Pb metal in water samples of the Tallo River in South Sulawesi, obtained an adsorption effectiveness of 96.4%. Overall, chitosan from squid internal shells has the potential as a heavy metal adsorbent in water filtration applications. This study opens up new opportunities in the development of natural materials for sustainable water treatment technology.